Uncertainty and the labour market : recent developments in job-search theory - McKenna, C. J. (New York : St. Martin's Press, 1985)
The book covers: Search Processes; Basic Model of Sequential Job Search; Extensions; The Firm in an Uncertain Labour Market; Empirical Implications; Contributions to Microeconomic Theory and Contributions to Macroeconomic Theory. The book may be read by advanced undergraduates, graduates students and their teachers. Mathematics has been used only where necessary to prepare the reader for some of the analytical tools used in the literature.
Includes index.
Includes bibliographical references: p. [155]-163.
rpm 09/04/2019, ijb, 31/01/2019
Loans
Keywords: Unemployed; Labor supply; Job hunting